Economic and ecological benefits of thermal insulation of external partitions depending on the temperature in residential premises. (15th January 2023) - Adamczyk, Janusz; Dylewski, Robert; Sobierajewicz, Piotr
Abstract: The building's energy demand for heating significantly depends on many parameters of the building, also on the climate zone. To determine this demand, the technical parameters of the building as well as functional parameters and the associated temperatures to be maintained inside the building are usually adopted. The article proposes a methodology for assessing both economic and ecological benefits resulting from changing the user profile and thermal insulation performance. The balances of ecological benefits were analysed in accordance with the idea of sustainable development by adopting model residential buildings, taking into account the year of construction of the building, the type of heat source and thermal insulation, and five types of room user profiles, considering technical and social requirements. The research on the impact of changing the user profile shows that lowering thermal comfort always brings economic and ecological benefits. In the case of thermal insulation, despite the reduction of the building's heat demand, the balance of benefits and costs is always positive only in the ecological aspect. For economic reasons, the balance does not have to be positive (in Polish conditions), due to the high economic costs of thermal insulation. Assuming that users are willing to accept lower thermal comfort, a user profile with a lower temperature can be recommended for economic and ecological benefits, or a profile reduction including the performance of thermal insulation. The above approach has a significant social dimension when rationalizing expenditure on thermal modernization of buildings, especially in energy and economic poverty areas. The suggestion, resulting from the study, of changing our habits to high temperatures in living quarters, can largely contribute to the improvement of the state of the environment, but also have a significant impact on the savings of energy resources. Lowering the temperature in the rooms from 23 °C to 17 °C reduces the energy demand for heating by up to about 40%. Highlights: Methodology for assessing benefits resulting from changing the user profile. Economic and ecological benefits of thermal insulation and changing the user profile. The year of construction of the building and the type of heat source were considered. Five types of room user profiles are included. The balance of benefits and costs is always positive only in the ecological aspect.